1996
DOI: 10.1021/la950904b
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Enhancement of CaCO3Dissolution during Scanning Force Microscopy

Abstract: We report scanning force microscope (SFM) observations of enhanced calcite dissolution in aqueous solution due to mechanical stimulation induced by the SFM tip. Images and mechanical treatment were performed in saturated (≥60 μM) CaCO3 solution adjusted to pH ∼9. Small area scans of monolayer steps significantly increase the step velocity in the scanned area (in the direction corresponding to dissolution) when the applied contact force is above about 160 nN for the tips employed. The step velocity could be inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 12 publications
6
43
0
Order By: Relevance
“…This image shows the characteristic rhombohedral etch pits associated with the dissolution of calcite in solution that is at least initially undersaturated with respect to the calcite. The ex situ image shown here and in situ images acquired at similar conditions in prior studies [20] are qualitatively similar, suggesting that the surface is not being altered upon removal from solution. The specifics of the dissolution kinetics that lead to the step structures associated with the etch pits have been well studied in prior research [20][21][22][23][24].…”
Section: Atomic Force Microscopysupporting
confidence: 71%
“…This image shows the characteristic rhombohedral etch pits associated with the dissolution of calcite in solution that is at least initially undersaturated with respect to the calcite. The ex situ image shown here and in situ images acquired at similar conditions in prior studies [20] are qualitatively similar, suggesting that the surface is not being altered upon removal from solution. The specifics of the dissolution kinetics that lead to the step structures associated with the etch pits have been well studied in prior research [20][21][22][23][24].…”
Section: Atomic Force Microscopysupporting
confidence: 71%
“…6 While there have been many nanometer scale studies of friction in the elastic, wearless low-load regime, relatively few studies on that scale deal with the wear regime. Wear due to transfer of atoms has been observed by Park et al 7 for calcite crystals in solution, by Kopta et al for muscovite mica in air, 8 by Gnecco et al for KBr in UHV, 9 and by Helt et al for muscovite mica in solution. 10 These studies found that atomic scale wear can result from the enhanced chemical activity of the surface due to lowering of the activation barrier for reaction by the applied load as well as by electrochemical potentials.…”
Section: Introductionmentioning
confidence: 81%
“…However, Park et al have recently demonstrated that probe-sample contact forces lead to strain-enhanced nucleation of double kinks on calcite steps as manifested by dissolution rates which increase exponentially with contact force. 15,16 Furthermore, they show that fast steps are much more susceptible to scanning-enhanced dissolution than slow steps, but only at higher contact force. 16 While the 50 nN contact forces used here may enhance dissolution somewhat, it is unlikely that this is the sole cause of the morphologies reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of papers have been published which address the rounding of the fast-fast corner under certain reaction conditions. 6,14,[15][16][17] Factors influencing the asymmetry include the presence of impurities which selectively impair kink propagation 14,15 as well as experimental effects such as flow rate which determine whether the dissolution process is controlled by diffusion through the unstirred boundary layer or by surface reaction. 6,14 Baer et al have observed the rounded fast-fast corner in nearly saturated solutions as well as in the presence of impurities and have attributed this phenomenon to the quenching of kink motion.…”
Section: Introductionmentioning
confidence: 99%